Desenvolvimento e validação de um novo protocolo para ciclagem térmica de materiais dentários - Marinho, Caroline Cotes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study aimed to evaluate the thermal variation that occurs in the oral environment; predicted the number of thermal cycles and temperature variation which occurs during certain time periods and compared the results of the bond strength of ceramic and luting agent after different aging protocols. For this purpose, six volunteers used a removable device with wireless thermal sensor and they were monitored for three days, to develop a new thermal cycling protocol. After this step, 40 feldspathic ceramic blocks were cemented together with a resin luting agent (N = 20), divided into five groups (n = 4) and cut into slices. Aging of the slices were: C, immediate test (without aging); A, storage in water for 30 days; E, thermal cycling experimental protocol developed in this study; CIB, storage of the slices in mouth for 30 days; and ISO, thermal cycling protocol established by ISO 11405 (2003). The slices were cut into sticks for microtensile test. The failure analysis were performed in a stereomicroscope. Maximum temperature observed was 47.59 ̊C, the lowest temperature was 13.11 ̊C. The average daily temperature is between 34 ̊C and 36 ̊C. The average temperature change per day was 5.3 times, with an average duration of 183 s. A, CIB, and E groups showed strength values statistically lower than C group (p-value = 0.0002), and they were similar among them. The ISO group was similar to the groups C and IB. The failure type most commonly found for all groups was mixed mode. It concluded that occurs daily 6 temperature variations, with duration of 180 seconds. The ISO thermocycling protocol did not reduce the bond strength. The experimental cycling used in E, 180 thermal cycles with a temperature range of 50 ̊C and 10 ̊C for 180 seconds each and 36 ̊C intermediate baths was able to accelerate the degradation process of bond between ceramic and cement that occurred during storage in water for 30 days

Este trabalho teve como objetivos: avaliar a variação térmica que ocorre em ambiente bucal para predizer a quantidade e duração das variações de temperatura por dia, a temperatura máxima e mínima encontrada na cavidade oral e sugerir um novo protocolo de ciclagem térmica baseado nestas informações; e comparar os resultados de resistência de união após várias formas de envelhecimento. Para tal, foi instalado um sensor térmico wireless no palato de um aparelho parcial removível de seis voluntários, e estes foram monitorados durante três dias para desenvolvimento de um novo protocolo de ciclagem térmica. Após esta etapa, 40 blocos de cerâmica feldspática foram cimentados entre si (N=20), divididos em cinco grupos (n=4) e cortados em fatias. As fatias foram submetidas aos seguintes tipos de envelhecimento: C, teste imediato (sem envelhecimento); A, armazenagem em água por 30 dias; E, protocolo de ciclagem térmica experimental desenvolvido neste estudo; CIB, ciclagem intra-bucal; e ISO, protocolo de ciclagem térmica estabelecido pela norma ISO 11405 (2003). As fatias foram cortadas em palitos, os quais foram submetidos ao teste de microtração. A análise de falha foi realizada com o auxílio de um estereomicroscópio. A temperatura máxima encontrada foi de 47,59 ̊C, a mínima foi de 13,11 ̊C. A média de temperatura diária manteve-se entre 34 ̊C e 36 ̊C. A média de variação de temperatura por dia foi de 5,3 vezes, com duração média de 183 s. Os grupos A, CIB, E apresentaram valores de resistência de união estatisticamente menor que o grupo C (p-valor=0,0002), sendo semelhantes entre si. O grupo ISO foi semelhante aos grupos C e CIB. O modo de falha mais encontrado para todos os grupos foi do tipo mista. Conclui-se que ocorrem em média 6 variações térmicas por dia, com duração de 180 segundos. O protocolo de ciclagem térmica sugerido pela ISO não foi capaz de reduzir a resistência de uniâo. A ciclagem..
Keywords: Cerâmicas odontológicas; Materiais dentários; Resistência à tração; Dental ceramics